Intracranial stenting as monotherapy in subarachnoid hemorrhage and sickle cell disease. (16th January 2012) - Ediriwickrema, Asiri; Williamson, Theresa; Hebert, Ryan; Matouk, Charles; Johnson, Michele H; Bulsara, Ketan R
Abstract : Introduction: Although there have been a few reports of coiling intracranial aneurysms in patients with sickle cell disease (SCD), there are no reports of intracranial stent placement in this patient population. A patient in whom stent placement was utilized as monotherapy to treat a blister-like aneurysm is described and the implications of SCD and endovascular treatment are discussed. Case report: A 37-year-old man with SCD presented with diffuse subarachnoid hemorrhage. Angiography confirmed a 2 mm irregular aneurysm on the posterior cerebral artery which was treated with an oversized Neuroform 3 stent that was placed across the aneurysm neck by the senior author (KRB). Follow-up CT angiography showed no residual aneurysmal filling. The patient was discharged home in a stable condition, and he continues to do well 4 weeks following the procedure with no recurrence of the aneurysm. Discussion: This report reviews hypercoagulability in SCD and the treatment options for intracranial aneurysms in patients with SCD. Additionally, the reported case suggests that intracranial stent placement may be a viable option for treating complex intracranial aneurysms in SCD patients.